Profitabilitas, Free Cash Flow, Dan Tax Planning Terhadap Firm Value: Moderasi Kualitas Laba Asia Tenggara - Rio Johan Putra; Novita Wijayanti (Media Akuntansi Perpajakan, 2026)
AbstractThis study examines the effects of profitability, free cash flow, and tax planning on firm value, with earnings quality as a moderating variable, among food and beverage companies in Southeast Asia. The sample comprises 50 companies from Indonesia, Malaysia, Singapore, Thailand, and the Philippines during 2022–2024, yielding 150 firm-year observations. Panel data were analyzed using the Fixed Effect Model and Moderated Regression Analysis. The results show that profitability has a positive and significant effect on firm value, while free cash flow and tax planning have significant negative effects. Earnings quality moderates the effects of free cash flow and tax planning on firm value, but does not moderate the effect of profitability. These findings highlight the role of earnings quality in shaping investor assessments of cash-flow management and tax strategies. Management should therefore strengthen reporting transparency and earnings quality when designing financial policies intended to enhance firm value.